Etude Techno-Economique d’une centrale hybride PV/Eolien à la région de EL KHNEG - KAOUKA Houssame; MECHRAOUI Ahmed Dhia; BOUCHIBA Oum El Kheir (Université Amar Thelidji- Laghouat FACULTE : Technologies DEPARTEMENT : Electrotechnique, 2022)
The main objective of this memorandum is the technical and economic study of a hybrid renewable energy plant (photovoltaic/wind) with a storage system based on fuel cells to secure the local needs of the station connected to the network. The existence of significant wind potential, through which the appropriate sizing methodology was presented, in addition to the value of the detailed cost of each part and the total cost, which confirmed that the study area is able to provide electricity at a very competitive price.
OPTION : Energies renouvelables en électrotechnique.